Stereotactic body radiotherapy with CyberKnife® System for low- and intermediate-risk prostate cancer: clinical outcomes and toxicities of CyPro Trial - Borzillo, Valentina; Scipilliti, Esmeralda; Pezzulla, Donato; Serra, Marcello; Ametrano, Gianluca; Quarto, Giuseppe; Perdonà, Sisto; Rossetti, Sabrina; Pignata, Sandro; Crispo, Anna; Di Gennaro, Piergiacomo; D’Alesio, Valentina; et al. (Frontiers in Oncology, 2023)
Abstract: Aims: Stereotactic body radiation therapy (SBRT) is an emerging therapeutic approach for low- and intermediate-risk prostate cancer. We present retrospective data on biochemical control, toxicity, quality of life of Trial CyPro. Materials and methods: 122 patients with low- and intermediate-risk prostate cancer were treated with the Cyberknife system at a dose of 35 or 36.25 Gy in five fractions. Biochemical failures (BF)/biochemical disease-free survival (bDFS) were defined using the Phoenix method (nadir + 2 ng/mL). Acute/late rectal and urinary toxicity were assessed by the Radiation Therapy Oncology Group (RTOG) toxicity scale. Quality of life (QoL) was assessed by EORTC QLQ C30 and PR25. International Erectile Function Index-5 (IIEF5) and International Prostatic Symptoms Score (IPSS) questionnaires administered at baseline, every three months after treatment during the first years and then at 24 and 36 months. Results: The 1, 2, and 5-year DFS were 92.9%, 92.9%, and 92.3%, respectively, while the 1, 2, and 5-year bDFS were 100%, 100%, and 95.7%, respectively . With regards to risk groups or doses, no statistically significant differences were found in terms of DFS or bDFS. Grade 2 urinary toxicity was acute in 10% and delayed in 2% of patients. No Grade 3 acute and late urinary toxicity was observed. Grade 2 rectal toxicity was acute in 8% and late in 1% of patients. No grade 3-4 acute and late rectal toxicity were observed. Grade 2 acute toxicity appeared higher in the high-dose group (20% in the 36.25Gy group versus 3% in the 35Gy group), but was not statistically significant. Conclusion: Our study confirms that Stereotactic Body Radiation Therapy (SBRT) of 35-36.25 Gy in five fractions with the CyberKnife system produces excellent control with low toxicity in patients with low-intermediate-risk prostate cancer. We found no dose-related differences in biochemical control and overall survival. Further confirmation of these results is awaited through the prospective phase of this study, which is still ongoing.